DUOLINGO: AN ENCHANTING APPLICATION TO LEARN ENGLISH FOR COLLEGE STUDENTS - Diah Permatasari; Farida Aryani (English Language Education Study Program Association (ELESPA) or Asosiasi Program Studi Pendidikan Bahasa Inggris (APSPBI), Indonesia, 2023)
Technology in learning is increasingly used as a medium, especially in learning English. This rapid development has also significantly impacted the gamification concept, which has begun to penetrate digitally. Duolingo, the game-based world's wildly popular language-learning app, is one of those impacts. This paper aims to find out the use of Duolingo in learning English by college students. The method of this study is qualitative, with a questionnaire as the instrument to collect the data. The participants are students from several universities in Indonesia. The study reveals that, Duolingo is considered an application that greatly supports college students in learning English and is an application that has effective innovation amid the rapid development of technology.